2017
DOI: 10.1016/j.foreco.2016.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Elevated light levels reduce hemlock woolly adelgid infestation and improve carbon balance of infested eastern hemlock seedlings

Abstract: The rapid loss of eastern hemlock (Tsuga canadensis) due to infestation with hemlock woolly adelgid (Adelges tsugae, HWA) has greatly altered structure and function of eastern forests. Numerous control strategies including local pesticide use and biocontrol with predator beetles have been implemented with considerable cost and varying success. Silviculture treatments that increase incident light on surviving hemlock trees to reduce infestation and ameliorate carbon starvation have been proposed as another poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…This reduced new branchlet growth is supported by Brantley et al [35] where they reported reduced photosynthetic efficiency and shorter branchlet length with reduced light levels. The effect of increased fertilizer in the current study was not as great as the effect of shade in increasing HWA density.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This reduced new branchlet growth is supported by Brantley et al [35] where they reported reduced photosynthetic efficiency and shorter branchlet length with reduced light levels. The effect of increased fertilizer in the current study was not as great as the effect of shade in increasing HWA density.…”
Section: Discussionsupporting
confidence: 53%
“…Brantley et al [35] also made a similar recommendation based on their studies of the effect of light on HWA and hemlocks. This could increase the mortality of summer aestivating sistens by exposing them to more solar radiation and increased temperatures leading to reduced HWA densities.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another mortality factor impacting HWA occurs during the summer due to high temperatures and possibly solar radiation. Higher HWA densities in low light conditions were found by Brantley [34], Sussky and Elkinton [69], Mayfield and Jetton [70], and Hickin and Preisser [71]. Mech [33] reported increased mortality of summer aestivating sistens with increases in temperature, particularly above 30 • C. McAvoy [35] reported that HWAs developing under shade had twice the survival rate compared to HWAs growing in full sun.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, subsequent generations of adelgids may also have been influenced by longer-term, indirect effects of sunlight mediated through the host plant. In artificial shade studies by Hickin and Preisser (2015) and Brantley et al (2017), eastern hemlock seedlings were exposed to shade treatments for several weeks or months prior to infestation, during which time host plants experienced sunlight-related effects on host physiology and chemistry. Hickin and Preisser (2015) found that shade increased the relative water content and water potential of eastern hemlock seedlings, and depending on time of measurement, decreased rates of transpiration and photosynthesis.…”
Section: Shade Cloth Experimentsmentioning
confidence: 99%